Novos dados sobre o tesouro do Monte do Senhor dos Perdidos (Penacova, Felgueiras) - Centeno, Rui M. S.; Pinto, José Marcelo Mendes (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Study of a set of 34 denarii, belonging to a hoard found in Monte do Senhor dos Perdidos (Penacova, Felgueiras), of which only 26 pieces were known (published in 1987). This material, from distinct private collections, makes it possible to establish a different chronology as far as its occultation is concerned (probably during the reigns of Claudius I or Nero).